Decentralizing agricultural public expenditures: Findings from a scoping study at the onset of a new stage in Ghana’s decentralization reform - Mogues, Tewodaj; Omusu-Baah, Kwaku (International Food Policy Research Institute, 2014)
This paper offers insights into the current status of agricultural expenditure decentralization and draws out the likely implications of this stage in the decentralization process for agricultural service delivery and national strategies.